Proteomics Study Reveals the Anti-Depressive Mechanisms and the Compatibility Advantage of Chaihu-Shugan-San in a Rat Model of Chronic Unpredictable Mild Stress - Zhu, Xiaofei; Li, Teng; Hu, En; Duan, Lihua; Zhang, Chunhu; Wang, Yang; Tang, Tao; Yang, Zhaoyu; Fan, Rong (Frontiers in Pharmacology, 2022)
Background: Chaihu-Shugan-Sanis a classical prescription to treat depression. According to the traditional Chinese medicine (TCM) principle, the 2 decomposed recipes in Chaihu-Shugan-San exert synergistic effects, including Shu Gan (stagnated Gan-Qi dispersion) and Rou Gan (Gan nourishment to alleviate pain). However, the specific mechanism of Chaihu-Shugan-San on depression and its compatibility rule remain to be explored. Objective: We aimed to explore the anti-depression mechanisms and analyze the advantage of TCM compatibility of Chaihu-Shugan-San. Methods: The chronic unpredictable mild stress (CUMS) rat model was established. Antidepressant effects were evaluated by sucrose preference test (SPT) and forced swimming test (FST). Tandem Mass Tag (TMT)-based quantitative proteomics of the hippocampus was used to obtain differentially expressed proteins (DEPs). Bioinformatics analysis including Gene Ontology (GO), pathway enrichment, and protein-protein interaction (PPI) networks was utilized to study the DEPs connections. At last, the achieved key targets were verified by western blotting. Results: Chaihu-Shugan-San increased weight gain and food intake, as well as exhibited better therapeutic effects including enhanced sucrose preference and extended immobility time when compared with its decomposed recipes. Proteomics showed Chaihu-Shugan-San, Shu Gan, and Rou Gan regulated 110, 12, and 407 DEPs, respectively. Compared with Shu Gan or Rou Gan alone, the expression of 22 new proteins was additionally changed by Chaihu-Shugan-San treatment, whereas the expression of 323 proteins whose expression was changed by Shu Gan or Rou Gan alone were not changed by Chaihu-Shugan-Santreatment. Bioinformatics analysis demonstrated that Chaihu-Shugan-San affected neurotransmitter's release and transmission cycle (e.g., γ-aminobutyric acid (GABA), glutamate, serotonin, norepinephrine, dopamine, and acetylcholine). GABA release pathway is also targeted by the 22 DEPs. Unexpectedly, only 2 pathways were enriched by the 323 DEPs: Metabolism and Cellular responses to external stimuli. Lastly, the expression of Gad2, Vamp2, and Pde2a was verified by western blotting. Conclusions: Chaihu-Shugan-San treats depression via multiple targets and pathways, which may include regulations of 110 DEPs and some neurotransmitter's transmission cycle. Compared with Shu Gan and Rou Gan, the 22 Chaihu-Shugan-San advanced proteins and the affected GABA pathway may be the advantages of Chaihu-Shugan-San compatibility. This research offers data and theory support for the clinical application of Chaihu-Shugan-San.